(3Ydi VhA GdJTQjY GdLRGFQj h GdeYGjjQ GdLRGFQjI ddJObjb (B- (3GdLRA GdChd (B-s - (3eMeO YHO GdeGLO(B, (3HhQcGjHs ((3GdLRGFQ(B:s (3OGQ EjdjGA ddfTQ hGdJhRjY(B,s, 2025)
(3jJMOK GdcJGH Mhd WHjYI JObjb GdMSGHGJ h GdgOa GdefhW Hg, JejjR JObjb GdMSGHGJ Yf CfhGY GdJObjb GdCNQi h YdGbI JObjb GdMSGHGJ HhXjaI GdJObjb GdOGNdj, GdEWGQ GdJfXjej degfI JObjb GdMSGHGJ aj GdLRGFQ h Shb NOeGJ JObjb GdMSGHGJ aj GdLRGFQ, eSDhdjGJ GdCWQGa Phj GdYdGbI HJObjb GdMSGHGJ, eYGjjQ JObjb GdMSGHGJ, COdI GdEKHGJ (B((3GdYfGUQ GdebfYI(B)(3, hKGFb GdJObjb h edaGJ GdJObjb, fXGe GdQbGHI GdOGNdjI, JbGQjQ eObb GdMSGHGJ(B. s
(3eQGLY U(B. 371-383s
Keywords: (3eQGLYI GdMSGHGJ(B- (3GdLRGFQs